'There is trauma all round': A qualitative study of health workers' experiences of caring for parents after stillbirth in Kenya and Uganda. Issue 1 (February 2023) - Mills, Tracey A.; Ayebare, Elizabeth; Mweteise, Jonan; Nabisere, Allen; Mukhwana, Raheli; Nendela, Anne; Omoni, Grace; Wakasiaka, Sabina; Lavender, Tina
Abstract: Background: Stillbirth is a traumatic life-event for parents. Compassionate care from health workers supports grief and adjustment, alleviating psychological distress and minimising serious adverse health and social consequences. Bereavement support in facilities in LMICs, including in sub-Saharan Africa, often fails to meet parents' needs. However, very few studies have explored health worker's experiences in these settings. Aim: To explore the lived experiences of midwives, doctors and others, caring for women after stillbirth in Kenya and Uganda. Methods: Qualitative, guided by Heideggerian phenomenology. Sixty-one health workers, including nurse-midwives (N = 37), midwives (N = 12) and doctors (N = 10), working in five facilities in Kenya and Uganda, were interviewed. Data were analysed following Van Manen's reflexive approach. Results: Three main themes summarised participants' experiences: ' In the mud and you learn to swim in it ' reflected a perceived of lack of preparation; skills were gained through experience and often without adequate support. The emotional and psychological impacts including sadness, frustration, guilt and shame were summarised in 'It's bad, it's a sad experience' . Deficiencies in organisational culture and support, which entrenched blame, fear and negative behaviours were encapsulated in Nobody asks 'how are you doing?' . Conclusion: Health workers in Kenya and Uganda were deeply sensitive to the impacts of stillbirth for women and families, and often profoundly and personally affected. Care and psychological support were acknowledged as often inadequate. Interventions to support improved bereavement care in sub-Saharan Africa need to target increasing health worker knowledge and awareness and also embed supportive organisational cultures and processes.